THE DEVELOPMENT OF ENGLISH TEXTBOOK BASED ON ADDIE MODEL AT PJKR STUDI PROGRAM PGRI UNIVERSITY OF BANYUWANGI (INFERENCE: Journal of English Language Teaching, 2026)
This study aimed to develop an English textbook for the Physical Education, Health, and Recreation (PJKR) Study Program using the ADDIE model. The research employed a research and development (R&D) approach, systematically implementing the Analysis, Design, Development, Implementation, and Evaluation stages. Needs analysis was conducted through questionnaires to identify students’ linguistic, pedagogical, and contextual requirements. The findings revealed the necessity for contextual, level-appropriate English materials emphasizing sports terminology, instructional language, academic reading, and professional communication. Based on these findings, the textbook was designed and developed with theme-based units, integrated language skills, contextual tasks, and visual supports relevant to the PJKR study program context. The textbook was then implemented through a limited try-out and evaluated by students, a material expert, and a language expert. The results showed that the textbook achieved a feasibility level of 78% from students (feasible), 74% from the material expert (feasible), and 82% from the language expert (very feasible). These results indicate that the developed textbook is pedagogically sound, relevant, and suitable for English textbook in PJKR Study Program. Overall, the study confirms that integrating ESP principles with the ADDIE model provides an effective framework for developing contextual, learner-centered instructional materials in higher education.
Keywords: R&D; English textbook; ADDIE model; Physical Education; Health and Recreation (PJKR) Study Program